The World of Coffee: 21st Century Solutions for A Commodity Facing Climate Change Risks - Negre, Laura (Consilience, 2023)
This paper examines the environmental impacts of climate change on the yields of Arabica coffee and the economic impacts on smallholder coffee farmers. To address these challenges, environmental and socio-economic solutions are proposed alongside a gap analysis of key coffee related certification programs. As temperatures increase, farmers are forced to move to higher elevations to grow coffee, where less land is available for farming. These climate change outcomes are visibly affecting Central and South American countries, which are experiencing up to 2°C of warming above pre-industrial averages (Sachs, 2019). Environmental risks may lead to smallholder farmers abandoning coffee production altogether, resulting in a decrease of supply and expertise for the coffee industry. At the same time, this industry is seeing increased demand from consumers for products with “green” certifications. Currently, sustainability certifications do not offer a full-fledged solution for environmental and socio-economic concerns. This gap analysis focuses on four main sustainability certifications and aims to provide an understanding of why certifications fail to address environmental and socio-economic challenges. This study seeks to identify the factors that certification models should incorporate in their supply chain assessments to examine climate change threats and improve outcomes for farmers. Analyzing the different criteria for certifications shows that: 1) Integrating environmental criteria within certifications is a resilient solution to addressing immediate climate change risks, and 2) mechanisms for protecting farmers against price volatility are required. The research shows that the Rainforest Alliance’s certification program is currently best positioned to serve the needs of an increasingly at-risk sector.